Principles Of Teaching Arabic Language In The Indian Context: Teachers’ View - Zubair K M A, Ahamed; Nadwi, A. Abdul Hai Hasani; Vijayakumar, S; Sathikulameen, A; Ali, M.Yasar Arafath (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Teaching a non-native language aims to equip students with fundamental language skills, including reading, writing, listening, and speaking. This investigation concentrates on enhancing the teaching of Arabic in India. Based on a qualitative study employing descriptive experiential analysis, this paper proposes strategies for teaching Arabic as a foreign language in Tamil Nadu, India, and discusses associated challenges. Papers presented at conferences in India, Sri Lanka, and Indonesia, as well as relevant journal articles, books, and research papers, were mined for data. The study provides a comprehensive case analysis of a highly experienced Arabic instructor and identifies essential principles for effective Arabic instruction. Findings indicate areas for development in the pedagogical competence of Arabic professors in colleges and universities in Tamil Nadu, highlighting the need for greater teaching awareness. Nonetheless, the study highlights the ability of dedicated instructors to foster a rich learning environment. This research provides insights that can be implemented to enhance Arabic language education in India, leading to a more effective and engaging learning environment for students.